Crimean Congo Hemorrhagic Fever in Eastern Turkey: Epidemiological and Clinical Evaluation - Tartar, Ayşe Sağmak; Balın, Şafak Özer; Akbulut, Ayhan; Demirdağ, Kutbeddin (Galenos Publishing House, 2019)
Objective: The present study aimed to evaluate Crimean-Congo Haemorrhagic Fever (CCHF) in patients hospitalized in our hospital. Methods: A total of 61 adult patients who were diagnosed as having CCHF between January 2011 and August 2018, in whom the diagnosis was confirmed by detecting virus-specific IgM by ELISA and/or by showing viral RNA by RT-PCR and who were managed at our clinic were evaluated retrospectively for their epidemiological and clinical findings, treatment and prognosis. Results: Of the 61 cases, 41 (67.2%) were male and 20 (32.8%) female. The mean age of the patients was 45.31±2.12 years. Sixty (98.4%) patients were living in rural area. Forty four patients (72.1 %) had a tick-bite history. According to months, most of the cases were seen in June, July and May, respectively. Fever, weakness and loss of appetite were the most common complaints of the patients. Treatment of ribavirin was started on the day of admission in all patients. One patient who was admitted in the late period died. The other 60 patients were discharged after being healed. Conclusions: Especially during summers when the disease is seen frequently, the history of tick contact should be questioned and tick should be searched in the examination in the patients with suspected clinical findings. A significant number of the patients do not have a known tick contact. Therefore, training meetings should be organized about the symptoms and findings of the disease in the endemic areas and awareness should be raised among the community and the doctors working in emergency services and primary care. © 2018 Turkish Society for Parasitology.
Türkiye’nin Doğusunda Kırım Kongo Kanamalı Ateşi: Epidemiyolojik ve Klinik Değerlendirme
Keywords: Crimean-Congo Haemorrhagic Fever; epidemiology; tick borne disease